Dengue virus transovarial transmission detection in Aedes aegypti from dengue hemorrhagic fever patients' residences in Denpasar, Bali - I. Made Sudarmaja; I. Kadek Swastika; Luh Putu Eka Diarthini; I. Putu Dema Prasetya; I. Md. Ady Wirawan (Veterinary World, 2022)
Background and Aim: To effectively control dengue hemorrhagic fever (DHF), it is necessary to assess the risk of vertical virus transmission in Aedes aegypti mosquitoes. This study aimed to detect dengue virus (DENV) transovarial transmission in A. aegypti collected from DHF patients' residences in Denpasar, Bali.